Tabbiejack 2 years ago Simplify the expression. √6(√33+7) A. √39+7√6 B. √198+7 C. 3√22+7√6 D. √198+7√6

1. Tabbiejack

2. Tabbiejack

I got C

3. Jhannybean

oh my goodness.bad mistake.

4. Jhannybean

it's not sqrt{37} it's sqrt{33} -_-

5. Tabbiejack

so the answer is not c then

6. Jhannybean

$\large \sqrt{6}(\sqrt{33}+7)$$\large \sqrt{a}*\sqrt{b} \implies \sqrt{6}*\sqrt{33}=\sqrt{198}$$\large \sqrt{6}*7 \implies 7\sqrt{6}$altogether $\large \sqrt{6}(\sqrt{33}+7)= \sqrt{198}+7\sqrt{6}$

7. Tabbiejack

o ok thanks so much

8. Jhannybean

Sorry about that... i wrote $$\sqrt{37}$$ instead of $$\sqrt{33}$$

9. Tabbiejack

so you saying it was D and that is not write

10. Tabbiejack

right sorry

11. Tabbiejack

it came up wrong

12. Jhannybean

it came up wrong? how come?

13. saifoo.khan

OMG! Jaan baji made a mistake!! =D

$\Huge \color{Red}{\bf \bigstar}$

15. Jhannybean

You are right @Tabbiejack .$\large \sqrt{198} = \sqrt{18*11} = \sqrt{9*2*11} = \sqrt{3*3*2*11} = 3\sqrt{22}$ So this would be $\large 3 \sqrt{22}+7\sqrt{6}$ goodjob.